Effect of Roughness on Flexural Strength of Dental Lithium-Disilicate. (2022) - Alves, M.F.R.P.; Simba, B.G.; Fernandes, M.H.V.; Elias, C.N.; Amarante, J.E.V.; Santos, C.
Abstract : Purpose/Aim: A common process in dental clinics is to perform small fitting adjustments of dentures after testing in the patient's mouth using the micro-grinding tool. This procedure promotes a local roughness increase and can lead to the formation of microcracks on the prosthesis surface. The aim of this work was to investigate the benefits of a post-finishing heat treatment on the surface roughness smoothing and crack healing of lithium disilicate dental glass ceramics, and its effect on the flexural strength. Materials and Methods: Commercially available lithium metasilicate, Li2 SiO3 (IPS e-maxCAD), samples were heat treated at 840C-7min. The material was characterized by X-ray diffraction, Scanning Electron Microscopy, Vickers hardness, Youngs modulus and fracture toughness. One of the surfaces of the samples was machined, aiming to simulate the fitting procedure of dentures in the dentist's laboratory, generating a rough surface. Half of the samples were tested by biaxial flexural testing (3B-P) and the other half were submitted to a rapid heat treatment (840C-3min) and later tested by biaxial strength, with statistical analysis by Weibull. The Roughness parameters (Ra, PV and Rz) were measured using Zygo New View 7100 Optical Profiler. Results: After the crystallization heat-treatment protocol suggested by the manufacturer, the formation of elongated lithium disilicate crystals, Li2 Si2 O5, with 36% residual amorphous phase was observed. In addition, the Vickers hardness of 6.1±0.3 GPa, fracture toughness of 1.90± 0.2 MPa.m1/2 and modulus of elasticity values of 91 ±2 GPa were obtained. The samples from the group without rapid heat-treatment showed bending strength of 203.5 ±33 MPa, with roughness values of Ra=0.6 ±0.2 μm, Rz=22 ±6 μm and PV=28 ±7 μm. After the rapid heat treatment, the roughness parameters Ra, Rz and PV were 0.3 ±0.2 μm, 9 ±6 μm and 5 ±4 μm, respectively. With this reduction in roughness, the flexural strength increased by 65%, with mean values of 336.6 ±32 MPa. Weibull modulus values were in the order of 5 for both groups. Conclusions: In the need for finishing machining of lithium disilicate-based glass-ceramic dental prostheses, the use of a rapid heat treatment at 840 C allows considerable gains in flexural strength. Increasing the service life of the prosthesis, due to a reduction on the surface roughness, promoted by the softening of the remaining amorphous phase in the glass-ceramic.